Epigenetic silencing and CRISPR-mediated reactivation of tight junction protein claudin10b (CLDN10B) in renal cancer - Sarah Arroyo Villora; Yufen Zhao; Paula Castellanos Silva; Alba A. Hahn; Vivien Olanin; David Groll; Sandra Maurer; Vera Roetzer; Witold Szymanski; Tara Procida-Kowalski; Niklas Philipp; Aline Koch; et al. (Clinical Epigenetics)
Abstract Background The kidney’s tubular system relies on cell polarity and tight junctions to maintain structure and function and disruptions contribute to diseases like cancer. Loss of tight junction proteins such as Claudins can actively contribute to tumorigenesis. Results We aimed to identify biomarkers for renal carcinoma, after kidney transplantation and conventional kidney tumors. We identified the epigenetic silencing of the Claudin 10 gene isoform B (CLDN10B) through DNA hypermethylation in renal cancers, including clear cell (ccRCC), papillary (pRCC) and post-transplantation renal carcinoma (PT-ccRCC). In contrast, CLDN10A was hypomethylated in ccRCC and pRCC. Differential methylation of the isoforms discriminates RCC from other malignancies. The epigenetic alteration of CLDN10B significantly correlated with reduced patient survival and advanced tumor staging. CLDN10B overexpression or induction significantly inhibited migration, cell cycle progression, and cellular growth. Using a CRISPR-based epigenetic editing tool reactivated CLDN10B to its endogenous level using VP160 and TET1 by promoter demethylation and significantly demonstrated its tumor-suppressive effects in 2D and 3D cell models. Conclusion Our findings suggest that CLDN10B acts as a tumor suppressor, and its epigenetic regulation may represent a therapeutic target for RCC. Ultimately, understanding CLDN10B’s regulation and function could provide new insights into renal cancer treatment.